1966
DOI: 10.1161/01.cir.33.6.862
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Venous and Arterial Hypertension due to Chronic Fibrous Mediastinitis

Abstract: A patient with chronic fibrous mediastinitis presented with bronchial, superior vena caval, and pulmonary venous obstruction, pulmonary hypertension, and pulmonary fibrosis. Pulmonary venous obstruction was confirmed at surgery and explains the hemodynamic findings of elevated pulmonary artery and pulmonary wedge pressures despite low left atrial pressure. Pulmonary function studies showed marked alterations in ventilation-distribution, diffusion, work of breathing, and fixed airway resistance. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Pulmonary function results depend on the type and extent of occlusion and provide an overall assessment of ventilatory impairment. 2 Magnetic resonance imaging of the chest and positron emission tomography (PET) in the assessment and management of FM may provide additional information about disease location and activity but needs more study.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary function results depend on the type and extent of occlusion and provide an overall assessment of ventilatory impairment. 2 Magnetic resonance imaging of the chest and positron emission tomography (PET) in the assessment and management of FM may provide additional information about disease location and activity but needs more study.…”
Section: Assessmentmentioning
confidence: 99%
“…1 The pathological findings typically include thick, "woody," hard fibrotic tissue encasing mediastinal structures, occasionally extending into the interlobular and interalveolar septa of the lung parenchyma and thickening the mediastinal pleura. 2,3 This fibrous tissue can compress and obstruct pulmonary vessels, the trachea and bronchi, and the esophagus. 2 The etiology of FM is diverse; it has been most commonly associated with fungal infections, especially with histoplasmosis in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superior vena cava obstruction is the most commonly reported and is easily diagnosed. Pulmonary artery obstruction has also been reported [3][4][5][6]. In sarcoidosis, two cases were reported by HAMILTON-CRAIG et al [7] who were successfully treated by stent placement in the pulmonary arteries.…”
mentioning
confidence: 90%
“…Regarding sarcoidosis, DEVARAJ et al [2] reported two cases in a series of 12 patients, with CT images and histology of fibrosing mediastinitis (16.6% of patients). Vascular obstruction due to fibrosing mediastinitis is frequent [3][4][5][6][7][8][9][10][11][12][13], particularly during histoplasmosis. Superior vena cava obstruction is the most commonly reported and is easily diagnosed.…”
mentioning
confidence: 99%